MODIFICATION OF ACTIVE-CHEMICALLY POLYURETHANES BY POLY(VINYLBENZYL-N-METHYL-D-GLUCAMINE) FOR BORON RETENTION - Palencia, Manuel (2016)
Boron is an essential micronutrient for the development, strengthening and growth of the plants; however, range essentiality of this element is narrow producing that its determination in the soils is an aspect very important to warrant its phytoavailability within an optimum concentration range. At the present, the development of polymer materials based in polyurethanes (PUs) with controlled capacity of uptake and release, high weatherability, and which permit controlled extraction and dosing of boron from irrigation water are of great interest for applications in agriculture. Thus, the objective of this study was to develop grafting polymers based in N-methyl-D-glucamine (NMDG) from active-chemically PU matrixes with boron retention properties. For that, vinyl-benzyl-N-methyl-D-glucamine (VBNMDG) was synthesized from vinylbenzyl chloride and NMDG. Later, urethanization of VBNMDG was performed by the reaction with methylene-diphenyl-diisocyanate (MDI); resulting PU has reactive groups capable to react in a second stage by free radical polymerization to produce grafting polymers with NMDG chains. Finally, boron retention capacity was determined by azomethine-H method. Results show that these materials have boron retention capacity and that these can potentially be used for agricultural fertilization with it.